POLA PENGAMBILAN KEPUTUSAN SEKOLAH DALAM PENINGKATAN MUTU PENDIDIKAN (STUDI KASUS DI SMA AL HIKMAH MUNCAR KABUPATEN BANYUWANGI) - Ahmad Aziz Fanani (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2016)
Decision making is the process of selecting a number of alternatives. Decision-making is of significant importance for the development level of the school. Appropriate decision will result in a change to the school for the better, but instead a less precise decision will adversely affect the school. This research is a field of research that is descriptive qualitative. Techniques in the determination of research subjects that I use is a sampling technique aims (purposive sampling). The decision making process in improving the quality of school education in SMA Al Hikmah Muncar done through consensus. Participatory decision-making, but does not involve the entire personnel of the school, because there is a separate management team in it, namely (principal, curriculum, student affairs, community relations, facilities and infrastructure, and Administration). Decision-making is done through measures that is long enough by identifying the problems and see the potential that exists, brainstorming (raises several alternatives) and take appropriate anternatif to implement and evaluate.